Pembaharuan KUHP Baru Terhadap Sistem Hukum Pidana di Indonesia - Widhy Andrian Pratama (Bandung Conference Series: Law Studies)
Abstract. The digital transformation of government services has made the authority to monitor and block illegal online content increasingly important. This authority becomes a criminal-law issue when employees use access within the blocking system to keep online gambling sites accessible. This research aims to analyze the criminal liability of employees or former employees of the Ministry of Communication and Digital Affairs who abused their authority to protect online gambling sites under Article 27 paragraph (2) of the Electronic Information and Transactions Law, and to analyze government efforts to combat online gambling through techno prevention and their comparison with Australia. The research uses a normative juridical method with statutory, conceptual, and case approaches. Secondary legal materials were obtained through library research and analyzed qualitatively. The main case is South Jakarta District Court Decision Number 279/Pid.Sus/2025/PN JKT.SEL. The findings show that the conduct is most appropriately qualified as intentionally and unlawfully making electronic information containing gambling content accessible. Abuse of authority is not treated as an independent offense in this construction, but is relevant to the unlawful or without-right element. Criminal liability depends on the fulfillment of the offense, intent, the absence of grounds excluding criminal liability, and each defendant's individual contribution within participation. Indonesia's techno prevention measures have produced significant quantitative results, but the Komdigi case demonstrates that technology must be accompanied by internal governance, access controls, audit trails, and accountability. Australia provides a useful comparative model through integrated regulation, a specialized regulator, technological blocking, monitoring, and public transparency.   Abstrak. Transformasi digital pemerintahan menjadikan kewenangan pemantauan dan pemblokiran konten ilegal semakin penting. Kewenangan tersebut menjadi persoalan hukum pidana ketika pegawai menggunakan akses dalam sistem pemblokiran untuk mempertahankan keteraksesan situs judi online. Penelitian ini bertujuan menganalisis pertanggungjawaban pidana pegawai atau mantan pegawai Kementerian Komunikasi dan Digital yang menyalahgunakan kewenangannya untuk melindungi situs judi online berdasarkan Pasal 27 ayat (2) Undang-Undang Informasi dan Transaksi Elektronik, serta menganalisis upaya pemerintah memberantas judi online melalui pendekatan techno prevention dan perbandingannya dengan Australia. Penelitian menggunakan metode yuridis normatif dengan pendekatan perundang-undangan, konseptual, dan kasus. Bahan hukum sekunder diperoleh melalui studi kepustakaan dan dianalisis secara kualitatif. Bahan hukum utama berupa Putusan Pengadilan Negeri Jakarta Selatan Nomor 279/Pid.Sus/2025/PN JKT.SEL. Hasil penelitian menunjukkan bahwa perbuatan para terdakwa paling tepat dikualifikasikan sebagai perbuatan dengan sengaja dan tanpa hak membuat dapat diaksesnya informasi elektronik yang memiliki muatan perjudian. Penyalahgunaan kewenangan tidak berdiri sebagai delik tersendiri dalam konstruksi tersebut, tetapi berkaitan dengan unsur tanpa hak. Pertanggungjawaban pidana ditentukan oleh terpenuhinya unsur delik, kesengajaan, tidak adanya alasan penghapus pidana, dan kontribusi individual masing-masing pelaku dalam penyertaan. Pendekatan techno prevention Indonesia telah menghasilkan capaian kuantitatif yang signifikan, tetapi perkara Komdigi menunjukkan bahwa teknologi harus disertai tata kelola internal, pembatasan akses, audit trail, dan akuntabilitas. Australia memberikan pembelajaran melalui integrasi regulasi, otoritas khusus, pemblokiran berbasis teknologi, pemantauan, dan transparansi publik.